-7(10+12r)-8(11-10r)=1-8r+1-6r

Simple and best practice solution for -7(10+12r)-8(11-10r)=1-8r+1-6r equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(10+12r)-8(11-10r)=1-8r+1-6r equation:


Simplifying
-7(10 + 12r) + -8(11 + -10r) = 1 + -8r + 1 + -6r
(10 * -7 + 12r * -7) + -8(11 + -10r) = 1 + -8r + 1 + -6r
(-70 + -84r) + -8(11 + -10r) = 1 + -8r + 1 + -6r
-70 + -84r + (11 * -8 + -10r * -8) = 1 + -8r + 1 + -6r
-70 + -84r + (-88 + 80r) = 1 + -8r + 1 + -6r

Reorder the terms:
-70 + -88 + -84r + 80r = 1 + -8r + 1 + -6r

Combine like terms: -70 + -88 = -158
-158 + -84r + 80r = 1 + -8r + 1 + -6r

Combine like terms: -84r + 80r = -4r
-158 + -4r = 1 + -8r + 1 + -6r

Reorder the terms:
-158 + -4r = 1 + 1 + -8r + -6r

Combine like terms: 1 + 1 = 2
-158 + -4r = 2 + -8r + -6r

Combine like terms: -8r + -6r = -14r
-158 + -4r = 2 + -14r

Solving
-158 + -4r = 2 + -14r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '14r' to each side of the equation.
-158 + -4r + 14r = 2 + -14r + 14r

Combine like terms: -4r + 14r = 10r
-158 + 10r = 2 + -14r + 14r

Combine like terms: -14r + 14r = 0
-158 + 10r = 2 + 0
-158 + 10r = 2

Add '158' to each side of the equation.
-158 + 158 + 10r = 2 + 158

Combine like terms: -158 + 158 = 0
0 + 10r = 2 + 158
10r = 2 + 158

Combine like terms: 2 + 158 = 160
10r = 160

Divide each side by '10'.
r = 16

Simplifying
r = 16

See similar equations:

| (21/5)*((-13/4)*p+5)=651/5 | | Y-5W=X | | 1/5+1/3 | | k-6/4=11 | | (5v+6)-5-3v=-15 | | 6m+k=b | | k-1/5=11 | | -6(6-x)+5=3(x-1) | | -7(6x+10)=266 | | 0.7p+0.2=-5/6p-1/5 | | 3btimesh=54 | | 3x^4-2y^4= | | -35/29+2y=-11 | | p+(p+28)+2(p-35)=661 | | x+1=-2x-14 | | -3x-8+44x=17 | | 25=15-2/3b | | 4y^2=-12y | | 4b-2=-4+4b+3 | | 600000000=b+(b+325000) | | 2-7y+4=3y+15-7y | | 2(1+5x)=9(x-5) | | x+x(.42)+x(1.16)=1811.0236 | | P^4/P^-5 | | -3(2+6r)=-6-2r | | -12b-11b= | | -20x+16y=4 | | 4x-3+7x-1= | | x+400+x(.42)+x(1.16)=4600 | | 111=16 | | 6y^2+23y+20=0 | | x(6x-5)=(6x+2)(x-1) |

Equations solver categories